Pengembangan Sistem Informasi Point of Sales (POS) berbasis Website untuk Manajemen Home Industry (Studi Kasus: Gelsey Real Surakarta) - Safria Isnibaiti; Issa Arwani; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Gelsey Real Surakarta is a home industry that is engaged in the business of buying and selling clothes. The increase in the number of sales by up to 50% from the beginning of 2021 to the middle of 2021 which makes them need more effort because they are recorded manually or recorded. The amount of data that must be written, they often do a re-calculation in the middle of 2021, when the soaring demand for production of up to Â±1000 orders per month creates sales results that are not balanced with the recording in the book. The small number of employees makes them do double jobs in the production and transaction departments. From these problems, Point of Sales (POS) information system was created for data management and sales transactions. The development of this system uses the Laravel framework and the programming language PHP, HTML, CSS, JavaScript and MySQL database. The tests used are functional testing, user acceptance testing and compatibility testing. Functional testing using a validation test results from this test obtained the results of 24 test cases which show all are valid. While the user acceptance testing test, the author submits a questionnaire with 18 total questions and the result is 91.11% where when adjusted to the Likert interval table, the examiner's assessment agrees with the questions in the questionnaire for information systems. The last test, namely the results of the compatibility testing test, shows that this system can be accessed by all web browsers. It can be concluded that the Point of Sales (POS) information system facilitates transaction management and also recaps data so that employees can minimize the occurrence of unintentional errors.